2016
DOI: 10.1038/srep37887
|View full text |Cite
|
Sign up to set email alerts
|

Non-RVD mutations that enhance the dynamics of the TAL repeat array along the superhelical axis improve TALEN genome editing efficacy

Abstract: Transcription activator-like effector (TALE) nuclease (TALEN) is widely used as a tool in genome editing. The DNA binding part of TALEN consists of a tandem array of TAL-repeats that form a right-handed superhelix. Each TAL-repeat recognises a specific base by the repeat variable diresidue (RVD) at positions 12 and 13. TALEN comprising the TAL-repeats with periodic mutations to residues at positions 4 and 32 (non-RVD sites) in each repeat (VT-TALE) exhibits increased efficacy in genome editing compared with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…For interrepeat VarSeTALEs the highly conserved leucine residue at position 29 ( Figure S1) was used as the breakpoint between repeats of different origins. Repeat subunits used in our intra-repeat VarSeTALEs correspond to secondary structural elements: short-helix (4-10), RVD loop (11)(12)(13)(14)(15), long-helix (16-28) and inter-repeat loop (29-1). Figure 1 illustrates the two design approaches using example sequences.…”
Section: Varsetale Repeat Arrays Contain Large Numbers Of Non-rvd Polmentioning
confidence: 99%
See 2 more Smart Citations
“…For interrepeat VarSeTALEs the highly conserved leucine residue at position 29 ( Figure S1) was used as the breakpoint between repeats of different origins. Repeat subunits used in our intra-repeat VarSeTALEs correspond to secondary structural elements: short-helix (4-10), RVD loop (11)(12)(13)(14)(15), long-helix (16-28) and inter-repeat loop (29-1). Figure 1 illustrates the two design approaches using example sequences.…”
Section: Varsetale Repeat Arrays Contain Large Numbers Of Non-rvd Polmentioning
confidence: 99%
“…Indeed, out of our initial set of 13 intra-repeat VarSeTALEs, most were very poor repressors, not significantly different from the negative control dTALE (Figure 2; dotted line). However, a recent study has also demonstrated that non-RVD polymorphisms that disrupt inter-repeat interactions can increase the structural flexibility of a dTALE repeat array superhelix, enhancing DNA binding 14 .…”
Section: Comparing Varsetale Design Approaches: Intra Vs Inter-repeatmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, further study of nonBSRs could be used to build rational design rules, helping users to select promising combinations. For example, a recent study used a mix of in vitro binding assays and molecular dynamics simulations to understand the functional impact of certain non-BSR polymorphisms at two positions within dTALE arrays (15). The VarSeTALE set in this study have poor resolution over some areas, e.g.…”
Section: Future Improvements To Varsetale Designmentioning
confidence: 99%
“…A recent study showed that repeat polymorphisms at two non-BSR positions can increase the binding affinity between a dTALE repeat array and its target DNA (15). Another study showed that extended TALE repeats, with additional non-BSR amino acids, can be used as a tool to provide optional target base skipping (16).…”
Section: Introductionmentioning
confidence: 99%